Persepsi Guru PAI terhadap Keefektifan Tes Objektif di SMA N 3 Sragen - Yayuk Riana; Ummu Hani; Veninda Gilang Ramadhan; Nurul Latifatul Inayati (CV. ITTC INDONESIA, 2024)
This research aims to examine the perceptions of PAI teachers at SMA N 3 Sragen in order to determine the effectiveness of using objective tests. This research uses a qualitative research method with a phenomenological approach. The data collection techniques used are through interviews and observation. The results of the research reveal that teachers can assess the effectiveness of using objective tests by giving questions to students according to the type of questions based on learning objectives so that they can adjust the questions they create. Research findings reveal that among the many types of objective tests are true-false tests, matching tests, and multiple choice tests. According to the informant, the PAI teacher at SMA N 3 Sukharjo in this school uses multiple choice tests in PAI subjects, and according to him it is very effective to use in learning models.